Penerapan Konsep Kota Pintar dengan Cara Penerapan ERP (Electronic Road Price) di Jalan Ibu Kota DKI Jakarta - Arman Syah Putra (Teknik Informatika Universitas Pamulang, 2020)
The problem raised in this research is the implementation of ERP (Electronic Road Price) which will be applied in several street corners of the capital of Jakarta, many pros and cons that will occur in its application, ranging from its licensing to its application in the field, socialization to users the road in the capital is very important to do because it will directly intersect with motorized motorists in the capital of Jakarta, in its application also must be considered using what tools are best placed in every corner of the capital to help smooth the system to be applied, in this research the author will provide suggestions and frameworks so that the implementation of the ERP system (Electronic Road Price) can be carried out right away, with the suggestions that have been made are expected to influence the policies that will be made in terms of ERP (Electronic Road Price) in the future.